Tradisi Tingkeban dalam Perspektif Pendidikan Islam di Nagari Persiapan Limau Puruik Kecamatan Kinali - Miftahul Jannah; Ahmad Rivauzi (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
This study aims to determine the values ​​of Islamic education in the tingkeban tradition in the Javanese tribal community in Nagari Preparation Limau Puruik, Kinali District, West Pasaman Regency. This research uses a qualitative approach with ethnographic methods. Researchers collect primary data from observations, interviews and secondary data from literature review. The sample in this study used a non-probability sampling technique with purposive nature with six informants. In this study, the author uses the technique of triagulation of source data. Data analysis techniques using data reduction, data presentation, and drawing conclusions. Data collection techniques using documentation, interviews, and observations. The results of this study are to determine the series of implementation of the tingkeban tradition and to find out that there has been a process of Islamization of the tingkeban tradition in Nagari Limau Puruik Preparation, the implementation of the tingkeban tradition has been flavored with Islamic values ​​consisting of aqidah, worship and moral values.